Why decentralization in Indonesia is not good for reducing women fertility? Results from National Socio Economic Survey 2002-2014 and a case study - Abrianty, Tria; Sujarwoto, Sujarwoto (FIA UB, 2017)
This study examines the relationship between decentralization and women fertility in Indonesia. Mixed methods combining multilevel analyses of National Survey Data (Susenas) 2002-2014 and a case study of Empat Lawang district were used to examine the relationship and to elaborate why fiscal, administrative and political decentralization do not contribute for reducing women fertility in the country. The findings show that decentralization in Indonesia do not contribute for reducing women fertility. It reveals that lack of district fiscal capacity, lack of competencies of street level bureaucrats, and lack of district mayor political commitment in family planning challenges the promises of decentralization for reducing women fertility. The findings conclude that decentralization in the country may not an effective way for reducing and controlling women fertility. The government may revitalize decentralized family planning and population control programs by addressing those three challenges.